Robust adaptive control of door opening by a mobile rescue manipulator based on unknown-force-related constraints estimation. Issue 1 (3rd May 2017) - Ding, Liang; Xia, Kerui; Gao, Haibo; Liu, Guangjun; Deng, Zongquan
SUMMARY: This study focuses on a door-opening mobile manipulator operating in four phases (reaching the door, grasping the door handle, turning the door handle, and pulling the door). We use force/torque feedback-based control, achieving compliance of the mobile base when it comes into contact with the handle. A method is proposed for estimating the unknown force-related constraints from manipulator joint position measurements. A robust adaptive control strategy is developed for tracking the planned trajectory to open the door. Finally, a mobile manipulator opens a real door with a locked latch and unknown force-related constraints, demonstrating the validity of the proposed approach.